Penerapan Metode Lean Six Sigma dalam Rangka Meningkatkan Kualitas Pelayanan di Perusahaan PT ID Express - Ramadan, Prima; Syarif, Abdul Azis; Ariani, Farida (Universitas Harapan Medan, 2022)
One of the things that become the basis for consumers to choose a company is the quality of service. The quality of service is important because it will have a direct impact on the company, especially companies engaged in the expedition sector. One type of service provided is timeliness of delivery. However, in practice the delivery time is not always on time, sometimes there are still delays in delivery. This study aims to identify the types of shipping problems that often occur and the factors that cause shipping problems and to design improvement strategies to minimize the occurrence of shipping problems. The method used in this study is the six sigma method with the DMAIC approach. Based on the research results, the type of problem that often occurs and needs to be addressed is the delay in delivery. Factors that cause delays in delivery are delays in stuffing plans, errors in informing delivery instructions to couriers, misunderstandings, shortage of manpower and unorganized workspaces. Strategies to minimize delays in the delivery of goods include adding manpower, working with focus and thoroughness, establishing active interactions between divisions, communicating various delivery information to couriers, and creating a comfortable and conducive atmosphere, as well as a neat working atmosphere.